Lithium-rich manganese-based positive electrode material and preparation method and application thereof
Through the solid reaction process of pre-decomposition heat treatment and segmented heat treatment, lithium-rich manganese-based positive electrode material with uniform grain size was prepared, which solved the problem of unsatisfactory improvement of the specific capacity of the existing materials, and improved the cycle stability and discharge capacity. , achieving higher energy density and safety performance.
Patent Information
- Application Number
- CN202411489078.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2024-12-13
AI Technical Summary
The specific capacity of the existing lithium-rich manganese-based positive electrode materials is not ideal, the first discharge efficiency is low, the material has safety hazards during the circulation process and poor rate performance, which hinders the commercial application of materials.
Through the sectional heat treatment of the transition metal carbonate precursor and the lithium source after predecomposition of heat treatment, a solid reaction is used to prepare a lithium-manganese-based positive electrode material, which limits the diffusion distance of lithium ions, inhibits abnormal growth of grains, and prepares crystallization A material with small and uniform particle size.
The charging and discharge capacity has been improved, the cycle stability has been improved, the discharge capacity has been significantly improved without sacrificing the charging capacity, and the safety performance and rate performance of the material have been improved.
Smart Images

Figure CN119118221A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-rich manganese-based positive electrode materials, and specifically relates to a lithium-rich manganese-based positive electrode material and a preparation method and application thereof. Background Art
[0002] As a chemical power source with high specific energy density, cyclic charging and discharging, and environmental friendliness, lithium-ion batteries have been widely used in 3C fields such as mobile phones and computers and have become one of the strong candidates for power sources for hybrid and pure electric vehicles. The energy density that can be achieved by common lithium-ion secondary batteries is <200 Wh / kg, which cannot meet the development requirements of pure electric vehicles. Therefore, the energy density of existing batteries needs to be greatly improved. The key factor in improving the energy density of lithium-ion batteries is to find high-energy-density positive electrode materials. According to the "2022-2027 China Lithium-Rich Manganese-Based Positive Electrode Materials Industry Market In-depth Research and Development Prospects Forecast Report", under the background of "carbon neutrality", the global new energy vehicle market penetration rate has increased rapidly, and the demand for power batteries is strong. The lithium-rich manganese-based positive electrode material has a high discharge specific capacity. It is one of the products with the highest discharge specific capacity among the known lithium-ion battery positive electrode materials. It is much higher than the common ternary materials and lithium iron phosphate positive electrode materials in the market. It can manufacture high-energy-density power batteries and improve the endurance of power batteries. Moreover, the cobalt and nickel content in the lithium-rich manganese-based positive electrode material is only about 30% of that in the ternary material, and it may also be cobalt-free, further reducing its cost, making it a highly promising next-generation lithium-ion battery positive electrode material.
[0003] However, in current research, the capacity of manganese-based cathode materials has not been fully utilized, and practical applications also face a series of problems: low initial discharge efficiency; oxygen evolution during the cycle, which poses a certain safety hazard; poor rate performance, etc. These problems have greatly hindered the commercial application of materials.
[0004] There are many methods to improve the specific capacity of lithium-rich manganese-based cathode materials, including adjusting components, surface coating, pickling treatment, and surface oxygen vacancies. The theoretical specific capacity of the material can be improved by adjusting the components, but the activation of the material is difficult and the capacity cannot be fully utilized; traditional surface modification technology can significantly improve the discharge efficiency, but it requires sacrificing a certain charge specific capacity, resulting in the first-cycle discharge specific capacity of lithium-rich manganese-based cathode materials still far less than the theoretical specific capacity. Summary of the invention
[0005] The purpose of the present invention is to provide a lithium-rich manganese-based positive electrode material and a preparation method and application thereof, so as to solve the technical problem that the traditional preparation method has unsatisfactory improvement in specific capacity.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a lithium-rich manganese-based cathode material, and the chemical formula of the lithium-rich manganese-based cathode material is xLi2MnO3∙(1-x)LiTMO2; wherein, 0 < x < 1, and TM is Ni, Co, and Mn.
[0007] Furthermore, the grain size of the lithium-rich manganese-based cathode material is 30 to 100 nm.
[0008] The present invention also discloses a preparation method of the above lithium-rich manganese-based cathode material, comprising the following steps: Pre-decompose and heat-treat the transition metal carbonate precursor to obtain a transition metal oxide precursor; After mixing the transition metal oxide precursor and the lithium source, perform segmented heat treatment to obtain the lithium-rich manganese-based cathode material.
[0009] Furthermore, the chemical formula of the transition metal carbonate precursor is Ni x Co y Mn z CO3; wherein, 0 < x < 1, 0 < y < 1, 0 < z < 1.
[0010] Furthermore, the process parameters of the pre-decomposition heat treatment are: Heat up at a heating rate of 2 to 8 °C / min to 450 °C to 850 °C and keep warm for 5 to 10 h.
[0011] Furthermore, the molar ratio of lithium in the lithium source to the transition metal atoms in the transition metal oxide precursor is 1.2 to 1.5.
[0012] Furthermore, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium oxide, lithium fluoride, and lithium sulfate.
[0013] Furthermore, the mixing method of the transition metal oxide precursor and the lithium source is ball milling.
[0014] Furthermore, the process parameters of the segmented heat treatment are: Heat up at a heating rate of 2 to 8 °C / min to 450 to 500 °C for sintering and keep warm for 4 - 8 h, and then heat up to 800 to 850 °C at the same heating rate and keep warm for 10 - 20 h.
[0015] The present invention also discloses the application of the above lithium-rich manganese-based cathode material in a lithium-ion battery.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a lithium-rich manganese-based positive electrode material. The lithium-rich manganese-based positive electrode material is prepared by mixing a transition metal carbonate precursor that has undergone a pre-decomposition heat treatment with a lithium source, performing a segmented heat treatment, and performing a solid-solid reaction. The diffusion distance of lithium ions during the synthesis process can be limited, thereby inhibiting the abnormal growth of grains, and preparing a lithium-rich manganese-based positive electrode material with a small and uniform grain size. The small grain size is conducive to the release of lithium ions during the charging process, thereby improving both the charging capacity and the discharging capacity.
[0017] Furthermore, the lithium-rich manganese-based positive electrode material prepared by solid-solid reaction has uniformly sized grains, which means that the grain boundaries are evenly distributed, and the grain boundaries are conducive to relieving the strain during the cycle and better releasing the stress, thereby improving the cycle stability. The method of the present invention can achieve an increase in discharge capacity without sacrificing charging or even increasing the charging capacity, which means that the material is expected to achieve a higher capacity breakthrough in combination with the existing mature surface modification process. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The present invention is a flow chart of the preparation process of the lithium-rich manganese-based positive electrode material; Figure 2 The X-ray diffraction patterns of the transition metal carbonate precursor of the present invention under different pre-decomposition heat treatment conditions; Figure 3 The scanning electron micrographs of transition metal carbonate precursors and transition metal oxide precursors under different pre-decomposition heat treatment conditions; Figure 4 X-ray diffraction patterns of the high-capacity lithium-rich manganese-based positive electrode materials described in Examples 13-17 and the lithium-rich manganese-based positive electrode materials described in Comparative Examples 1-3; Figure 5 Scanning electron microscopic morphology images of the high-capacity lithium-rich manganese-based positive electrode materials described in Examples 13, 16, and 17 and the lithium-rich manganese-based positive electrode materials described in Comparative Examples 1-3; Figure 6 The first cycle charge and discharge curves of the high-capacity lithium-rich manganese-based positive electrode materials described in Examples 16-19 and the lithium-rich manganese-based positive electrode materials described in Comparative Examples 1 and 3 at a current density of 0.1C and a voltage range of 2.0-4.8V; Figure 7 This is a comparison chart of the cycle performance of the high-capacity lithium-rich manganese-based positive electrode material described in Example 16 and the lithium-rich manganese-based positive electrode material described in Comparative Example 1 at a current density of 0.33C and a voltage range of 2.0-4.6V. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0020] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0021] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0022] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0023] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0024] like Figure 1 As shown, the present invention discloses a method for preparing a lithium-rich manganese-based positive electrode material, which mainly includes the following steps: placing a transition metal carbonate precursor in a muffle furnace for pre-decomposition heat treatment to obtain a transition metal oxide precursor; The transition metal oxide precursor and the lithium source are ball-milled and mixed evenly, and then the mixture is placed in a muffle furnace for segmented heat treatment to obtain a high-capacity lithium-rich manganese-based positive electrode material.
[0025] Preferably, the chemical formula of the transition metal carbonate precursor is Ni x Co y Mn z CO3; of which 0 <x<1,0<y<1,0<z<1。
[0026] Preferably, the process parameters of the pre-decomposition heat treatment are: Heat up to 450°C - 850°C at a heating rate of 2 - 8°C / min and hold for 5 - 10 h.
[0027] Preferably, the molar ratio of lithium in the lithium source to transition metal atoms in the transition metal oxide precursor is 1.2 - 1.5.
[0028] Preferably, the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium oxide, lithium fluoride, and lithium sulfate. The process parameters of the segmented heat treatment are as follows: Heat up to 450 - 500°C at a heating rate of 2 - 8°C / min for sintering and hold for 4 - 8 h, then heat up to 800 - 850°C at the same heating rate and hold for 10 - 20 h.
[0029] Preferably, the mixing method of the transition metal oxide precursor and the lithium source is ball milling.
[0030] The chemical formula of the lithium-rich manganese-based cathode material disclosed in the present invention is xLi2MnO3∙(1 - x)LiTMO2; where 0 < x < 1, and TM is Ni, Co, and Mn.
[0031] The present invention also provides the application of the above lithium-rich manganese-based cathode material in a lithium-ion battery.
[0032] By improving the synthesis process of the material, the present invention pre-decomposes the transition metal carbonate precursor, and then combines it with a high-melting-point lithium source to achieve a complete solid-solid reaction to prepare a high-capacity lithium-rich manganese-based cathode material. Through the solid-solid reaction, the diffusion distance of lithium ions can be limited, thereby inhibiting the abnormal growth of grains, and preparing a lithium-rich manganese-based cathode material with small and uniform grain sizes. The small grain size is beneficial to the extraction of lithium ions during the charging process, thereby improving both the charging capacity and the discharging capacity. In addition, the smaller grains mean more grain boundaries, which is beneficial to alleviating the strain during the cycling process and better releasing stress, thereby improving the cycling stability.
[0033] The following further elaborates the present invention in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and not to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of this application.
[0034] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0035] Example 1 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was put into a crucible, placed in a muffle furnace, and heated to 400°C at a heating rate of 5°C / min and kept at this temperature for 5h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P01.
[0036] Example 2 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was put into a crucible, placed in a muffle furnace, and heated to 420°C at a heating rate of 5°C / min and kept at this temperature for 5h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P02.
[0037] Example 3 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was put into a crucible, placed in a muffle furnace, and heated to 440°C at a heating rate of 5°C / min and kept at this temperature for 5h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P03.
[0038] Example 4 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was put into a crucible, placed in a muffle furnace, and heated to 460°C at a heating rate of 5°C / min and kept at this temperature for 5h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P04.
[0039] Example 5 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was put into a crucible, placed in a muffle furnace, and heated to 400°C at a heating rate of 5°C / min and kept at this temperature for 5h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P05.
[0040] Example 6 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was put into a crucible, placed in a muffle furnace, and heated to 500°C at a heating rate of 5°C / min and kept at this temperature for 5h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P06.
[0041] Example 7 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6CO3 was put into a crucible, placed in a muffle furnace, and heated to 520°C at a heating rate of 5°C / min and kept at this temperature for 5h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P07.
[0042] Example 8 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was put into a crucible, placed in a muffle furnace, and heated to 540°C at a heating rate of 5°C / min and kept at this temperature for 5h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P08.
[0043] Example 9 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was put into a crucible, placed in a muffle furnace, and heated to 560°C at a heating rate of 5°C / min and kept at this temperature for 5h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P09.
[0044] Example 10 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was put into a crucible, placed in a muffle furnace, and heated to 580°C at a heating rate of 5°C / min and kept at this temperature for 5h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P10.
[0045] Embodiment 11 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was put into a crucible, placed in a muffle furnace, and heated to 600°C at a heating rate of 5°C / min and kept at this temperature for 5h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P11.
[0046] Example 12 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 was put into a crucible, placed in a muffle furnace, and heated to 850°C at a heating rate of 5°C / min and kept at this temperature for 10 h (pre-decomposition heat treatment) to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 O (transition metal oxide precursor), labeled as P12.
[0047] Example 13 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 8 Co 1 / 8 Mn 3 / 4 CO3 was put into a crucible, placed in a muffle furnace, and heated to 400°C at a heating rate of 5°C / min and kept at this temperature for 5h to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 8 Co 1 / 8Mn 3 / 4 O, marked as P13.
[0048] Embodiment 14 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 8 Co 1 / 8 Mn 3 / 4CO3 was put into a crucible, placed in a muffle furnace, and heated to 500°C at a heating rate of 5°C / min and kept at this temperature for 5h to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 8 Co 1 / 8Mn 3 / 4 O, marked as P14.
[0049] Embodiment 15 This embodiment provides a method for preparing a transition metal oxide precursor, comprising the following steps: Weigh 10 g of transition metal carbonate precursor Ni 1 / 8 Co 1 / 8 Mn 3 / 4 CO3 was put into a crucible, placed in a muffle furnace, and heated to 600°C at a heating rate of 5°C / min and kept at this temperature for 5h to obtain the pre-decomposed transition metal oxide precursor Ni 1 / 8 Co 1 / 8Mn 3 / 4 O, marked as P15.
[0050] Example 16 This embodiment discloses a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: Weigh 1.8 g of Li2O and mix with PO4, add into a jar mill at a speed of 50 rpm and ball mill for 5 h to obtain a uniform mixture; The mixture was placed in a crucible and placed in a muffle furnace. The temperature was first raised to 500°C at a heating rate of 5°C / min and sintered for 5 h. Then the temperature was raised to 830°C at the same heating rate and kept for 12 h to obtain a lithium-rich manganese-based cathode material with a small grain size (0.5Li2MnO3∙0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2).
[0051] Embodiment 17 This embodiment discloses a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: Weigh 4.4 g Li2CO3 and mix with PO4, add into a jar mill at a speed of 50 rpm and ball mill for 5 h to obtain a uniform mixture; The mixture was placed in a crucible and placed in a muffle furnace. The temperature was first raised to 500°C at a heating rate of 5°C / min and sintered for 5 h. Then the temperature was raised to 830°C at the same heating rate and kept for 12 h to obtain a lithium-rich manganese-based cathode material with a small grain size (0.5Li2MnO3∙0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2).
[0052] Embodiment 18 This embodiment discloses a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: Weigh 2.9 g LiOH and mix with PO4, add into a jar mill at a speed of 50 rpm and ball mill for 5 h to obtain a uniform mixture; The mixture was placed in a crucible and placed in a muffle furnace. The temperature was first raised to 500°C at a heating rate of 5°C / min and sintered for 5 h. Then the temperature was raised to 830°C at the same heating rate and kept for 12 h to obtain a lithium-rich manganese-based cathode material with a small grain size (0.5Li2MnO3∙0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2).
[0053] Embodiment 19 This embodiment discloses a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: Weigh 2.2 g Li2CO3, 0.9 g LiO and P06, mix them, add them into a jar mill at a speed of 50 rpm and ball mill for 5 h to obtain a uniform mixture; The mixture was placed in a crucible and placed in a muffle furnace. The temperature was first raised to 500°C at a heating rate of 5°C / min and sintered for 5 h. Then the temperature was raised to 830°C at the same heating rate and kept for 12 h to obtain a lithium-rich manganese-based cathode material with a small grain size (0.5Li2MnO3∙0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2).
[0054] Embodiment 20 This embodiment discloses a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: Weigh 2.2 g Li2CO3, 1.5 g LiOH and P06, mix them, add them into a jar mill at a speed of 50 rpm and ball mill for 5 h to obtain a uniform mixture; The mixture was placed in a crucible and placed in a muffle furnace. The temperature was first raised to 500°C at a heating rate of 5°C / min and sintered for 5 h. Then the temperature was raised to 830°C at the same heating rate and kept for 12 h to obtain a lithium-rich manganese-based cathode material with a small grain size (0.5Li2MnO3∙0.5LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2).
[0055] Embodiment 21 This embodiment discloses a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: Weigh 2.2 g Li2CO3, 1.6 g LiF and P14, mix them, add them into a jar mill at 50 rpm and mill for 5 h to obtain a uniform mixture; The mixture was placed in a crucible and placed in a muffle furnace. The temperature was first raised to 500°C at a heating rate of 5°C / min and sintered for 5 h. Then the temperature was raised to 830°C at the same heating rate and kept for 12 h to obtain a lithium-rich manganese-based cathode material with a small grain size (0.625Li2MnO3∙0.375LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2).
[0056] Embodiment 22 This embodiment discloses a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: Weigh 2.2 g Li2CO3 and 3.3 g Li2SO4 and mix with P14, add into a jar mill at 50 rpm and mill for 5 h to obtain a uniform mixture; The mixture was placed in a crucible and placed in a muffle furnace. The temperature was first raised to 500°C at a heating rate of 5°C / min and sintered for 5 h. Then the temperature was raised to 830°C at the same heating rate and kept for 12 h to obtain a lithium-rich manganese-based cathode material with a small grain size (0.625Li2MnO3∙0.375LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2).
[0057] Embodiment 23 This embodiment discloses a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: Weigh 2.2 g Li2CO3 and 3.3 g Li2SO4 and mix with P14, add into a jar mill at 50 rpm and mill for 5 h to obtain a uniform mixture; The mixture was placed in a crucible and placed in a muffle furnace. The temperature was first raised to 450°C at a heating rate of 2°C / min and sintered for 5 h. Then the temperature was raised to 850°C at the same heating rate and kept for 12 h. The lithium-rich manganese-based positive electrode material with a small grain size (0.625Li2MnO3∙0.375LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2).
[0058] Embodiment 24 This embodiment discloses a method for preparing a lithium-rich manganese-based positive electrode material, comprising the following steps: Weigh 2.2 g Li2CO3 and 3.3 g Li2SO4 and mix with P14, add into a jar mill at 50 rpm and mill for 5 h to obtain a uniform mixture; The mixture was placed in a crucible and placed in a muffle furnace. The temperature was first raised to 450°C at a heating rate of 8°C / min and sintered for 5 h. Then the temperature was raised to 800°C at the same heating rate and kept for 12 h to obtain a lithium-rich manganese-based positive electrode material with a small grain size (0.625Li2MnO3∙0.375LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2).
[0059] Comparative Example 1 A) Weigh 10g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 and 4.4 g Li2CO3 were added to a jar mill at 50 rpm and milled for 5 h to obtain a uniform mixture; B) The ball-milled uniform mixture is placed in a crucible, placed in a muffle furnace, first heated to 500°C at a heating rate of 5°C / min, sintered and kept warm for 5 hours, then heated to 830°C at the same heating rate and kept warm for 12 hours to obtain a lithium-rich manganese-based positive electrode material.
[0060] Comparative Example 2 This comparative example provides a preparation process of a lithium-rich manganese-based positive electrode material, which is as follows: A) Weigh 10g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 and 1.7 g Li2O were added to a jar mill at 50 rpm and milled for 5 h to obtain a uniform mixture; B) The ball-milled uniform mixture is placed in a crucible, placed in a muffle furnace, first heated to 500°C at a heating rate of 5°C / min, sintered and kept warm for 5 hours, then heated to 830°C at the same heating rate and kept warm for 12 hours to obtain a lithium-rich manganese-based positive electrode material.
[0061] Comparative Example 3 This comparative example provides a preparation process of a lithium-rich manganese-based positive electrode material, which is as follows: A) Weigh 10g of transition metal carbonate precursor Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3 and 2.9 g LiOH were added to a jar mill at 50 rpm and milled for 5 h to obtain a uniform mixture; B) The ball-milled uniform mixture is placed in a crucible, placed in a muffle furnace, first heated to 500°C at a heating rate of 5°C / min, sintered and kept warm for 5 hours, then heated to 830°C at the same heating rate and kept warm for 12 hours to obtain a lithium-rich manganese-based positive electrode material.
[0062] The positive electrode material prepared above is used to manufacture and assemble a lithium-ion secondary battery: The lithium-rich manganese-based positive electrode materials (Examples 16-24 and Comparative Examples 1-3) prepared above were mixed with a conductive agent (acetylene black) and a binder (PVDF) at a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone (solvent) was added to prepare an electrode slurry. The electrode slurry was then coated on an aluminum foil with a thickness of 8 μm, dried, rolled with a press, and then cut into discs with a diameter of 14 mm, weighed, vacuum dried, and transferred to a glove box for use.
[0063] The positive electrode, polyethylene separator, and lithium foil were stacked in sequence to form an R2032 button cell, into which 30 uL of electrolyte was injected and then packaged to serve as a lithium metal secondary battery.
[0064] Evaluation of lithium-ion secondary batteries: 1) Battery cycle capacity retention rate: Initial charge and discharge: The charge and discharge cut-off voltage of the assembled battery is 2.0-4.8V. At 25°C, charge to the upper voltage limit using a 0.1C constant current constant voltage charging method, and then discharge to the lower voltage limit using a 0.1C constant current. Perform this cycle for 3 times to stabilize the battery. Also, the current value of the rated capacity discharged in 1 hour is 1C.
[0065] Cycle test: For the battery that has been initially charged and discharged, 100 cycles were performed at 25°C as follows: charging at a constant current and constant voltage of 0.33C to an upper voltage limit of 4.6V, and then discharging at a constant current of 0.33C to a lower voltage limit of 2.0V. The ratio of the discharge capacity of the nth cycle to the discharge capacity of the first cycle at this time was taken as the capacity retention rate.
[0066] Table 1 shows the statistical data of the mass loss rate of transition metal carbonate precursors at different pre-decomposition temperatures. Table 1 shows the mass loss percentage of the material after being kept at different temperatures for 5 hours. The transition metal carbonate precursor will decompose and release CO2 under heating conditions. As the pre-decomposition temperature increases, the higher the degree of decomposition, the more thorough the CO2 release.
[0067] Table 1 Statistical data of mass loss rate of transition metal carbonate precursors at different predecomposition temperatures
[0068] Figure 2 The X-ray diffraction patterns of transition metal carbonate precursors under different pre-decomposition conditions are shown in the figure. The XRD patterns of the products after being kept at different temperatures for 5 hours can be seen. It can be seen that the intensity of the diffraction peak increases with the increase of the pre-decomposition temperature, indicating that the crystallinity of the material increases. In addition, new diffraction peaks appear with the increase of temperature. This is because the transition metal carbonate precursors not only undergo decomposition reactions during the pre-decomposition process, but also undergo oxidation reactions of transition metals. The oxidation degree of transition metals is different at different temperatures, resulting in different crystal structures of the final materials.
[0069] Figure 3 The scanning electron micrographs of transition metal carbonate precursors and transition metal oxide precursors under different pre-decomposition conditions are shown in the figure. The figure shows the morphology of transition metal carbonate precursors and transition metal oxide precursors pre-decomposed at 450℃-5h, 500℃-5h, and 850℃-10h, respectively. It can be seen that the surface morphology of the transition metal carbonate precursor particles is relatively rough, and the surface of the precursors pre-decomposed at 450℃ and 500℃ becomes more uniform and smooth. After the pre-decomposition treatment at 850℃, the morphology of the precursor has changed more significantly, because under the high-temperature thermodynamic drive, the crystal structure is transformed into a spinel structure due to the oxidation of the transition metal, and the grains grow rapidly.
[0070] Figure 4 The X-ray diffraction patterns of the high-capacity lithium-rich manganese-based positive electrode materials described in Examples 13-17 and the lithium-rich manganese-based positive electrode materials described in Comparative Examples 1-3. Figure 4 It can be seen that the XRD characteristic peak positions of the high-capacity lithium-rich manganese-based positive electrode material (the high-capacity lithium-rich manganese-based positive electrode material described in Examples 13-17) and the original lithium-rich manganese-based positive electrode material (the lithium-rich manganese-based positive electrode material described in Comparative Examples 1-3) are completely consistent, and there are no impurity peaks, and the (108) / (110) diffraction peak is obviously split, proving that the high-capacity lithium-rich manganese-based positive electrode material still maintains a good layered structure.
[0071] Figure 5 Scanning electron micrographs of the high-capacity lithium-rich manganese-based positive electrode materials described in Examples 13, 16, and 17 and the lithium-rich manganese-based positive electrode materials described in Comparative Examples 1-3. The morphological structures of all lithium-rich manganese-based positive electrode materials are shown as micron-spheres formed by stacking of primary particles. Comparison of the high-capacity lithium-rich manganese-based positive electrode materials of Examples 13, 16, and 17 with the lithium-rich manganese-based positive electrode materials of Comparative Examples 1-3 shows that the grain size distribution of the high-capacity lithium-rich manganese-based positive electrode materials is more uniform, within 100nm, and there are no abnormally large grains, while the grain size distribution area of the lithium-rich manganese-based positive electrode materials of Comparative Examples 1-3 is wider and larger, within 250nm, especially the lithium-rich manganese-based positive electrode material of Comparative Example 3 has abnormally large grains.
[0072] Figure 6 The first cycle charge and discharge curves of the high-capacity lithium-rich manganese-based positive electrode materials described in Examples 16-19 and the lithium-rich manganese-based positive electrode materials described in Comparative Examples 1 and 3 at a current density of 0.1C and a voltage range of 2.0-4.8V. Table 2 shows the data of the above curves. Figure 6 As can be seen from Table 2, the method of the present invention is effective in improving the charging capacity and discharging capacity of the lithium-rich manganese-based positive electrode material.
[0073] Table 2 First cycle charge and discharge data of high capacity lithium-rich manganese-based positive electrode materials described in Examples 16-19
[0074] Figure 7 This is a comparison chart of the cycle performance of the high-capacity lithium-rich manganese-based positive electrode material described in Example 16 and the lithium-rich manganese-based positive electrode material described in Comparative Example 1 at a current density of 0.33C and a voltage range of 2.0-4.6V (initial activation has been carried out at a current density of 0.1C and a voltage range of 2.0-4.8V). It can be seen that at 0.33C, the discharge specific capacity of the high-capacity lithium-rich manganese-based positive electrode material described in Example 16 can reach 257.9mAh / g, while the capacity of the lithium-rich manganese-based positive electrode material described in Comparative Example 1 under the same conditions is only 239.8mAh / g. After 100 cycles, the discharge specific capacity of the high-capacity lithium-rich manganese-based positive electrode material described in Example 16 is 232.1mAh / g, and the capacity retention rate is 90.00%; the specific capacity of Comparative Example 1 after 100 cycles is 213.1mAh / g, and the capacity retention rate is 88.87%. While Example 16 has a high discharge specific capacity, its cycle retention rate is still higher than that of Comparative Example 1. This is attributed to the fact that the present invention adopts a precursor pre-decomposition process and selects a matching lithium source to achieve a solid-solid reaction, thereby preparing a lithium-rich manganese-based positive electrode material with a uniform grain size distribution. During the charge and discharge process, the speed and degree of lithium ion deintercalation can be achieved, thereby improving the electrochemical properties of the material.
[0075] The lithium-rich manganese-based positive electrode material disclosed in the present invention has a high specific capacity, which far exceeds the discharge specific capacity of positive electrode materials such as lithium iron phosphate and ternary materials currently in commercial application; the preparation raw material used uses relatively cheap manganese as the main component, and the precious metal content is low. Compared with common lithium cobalt oxide and nickel-cobalt-manganese ternary positive electrode materials, the lithium-rich manganese-based material reduces the cost; in addition, no toxic or harmful materials are used in the production process, and there is no pollution to the environment; the application of the above-mentioned lithium-rich manganese-based positive electrode material can significantly improve the energy density, cycle life and safety performance of lithium-ion batteries, has the advantages of low cost and high energy density, and can be widely used in electric vehicles, energy storage fields, etc., broadening the application field of lithium-ion batteries, promoting the development and innovation of lithium-ion battery technology, and providing strong support for the further upgrading and optimization of lithium-ion batteries.
[0076] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A lithium-rich manganese-based positive electrode material, characterized in that: The chemical formula of the lithium-rich manganese-based cathode material is xLi2MnO3∙(1-x)LiTMO2; wherein, 0 < x < 1, and TM is Ni, Co, and Mn.
2. A lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The grain size of the lithium-rich manganese-based cathode material is 30 to 100 nm.
3. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 1 or 2, characterized in that: It includes the following steps: Pre-decompose and heat-treat the transition metal carbonate precursor to obtain a transition metal oxide precursor; After mixing the transition metal oxide precursor and the lithium source, perform segmented heat treatment to obtain the lithium-rich manganese-based cathode material.
4. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The chemical formula of the transition metal carbonate precursor is Ni x Co y Mn z CO3; Wherein, 0 < x < 1, 0 < y < 1, 0 < z < 1.
5. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The process parameters of the pre-decomposition heat treatment are: Heat up at a heating rate of 2 to 8 °C / min to 450 °C to 850 °C and keep warm for 5 to 10 h.
6. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The molar ratio of lithium in the lithium source to the transition metal atoms in the transition metal oxide precursor is 1.2 to 1.
5.
7. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium oxide, lithium fluoride, and lithium sulfate.
8. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The mixing method of the transition metal oxide precursor and the lithium source is ball milling.
9. The method for preparing a lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The process parameters of the segmented heat treatment are: Heat up at a heating rate of 2 to 8 °C / min to 450 to 500 °C for sintering and keep warm for 4 - 8 h, and then heat up to 800 to 850 °C at the same heating rate and keep warm for 10 - 20 h.
10. Use of the lithium-rich manganese-based positive electrode material according to claim 1 or 2 in lithium-ion batteries.
